EVALUATION STANDARD DOS OF MARCH AND CORPORAL POSTURE PRACTICING DOS OF THERAPEUTIC HORSEBACKRIDING WITH CEREBRAL PARALYSIS (Fiep Bulletin - online, 2014)
The therapeutic horsebackriding is indicated as therapy in the following cases: motor disorders caused by motoneurons injuries; cerebral injuries; evolutions and behavior disturbs and orthopedics pathologies (FREIRE, 1999). In this context, our objective of the present work was to evaluate the standard of walking and the corporal position, in practitioners of horsebackriding with cerebral paralysis, looking for to relate the walking and position with the practical work developed in the therapeutic horsebackriding Center. Participated on the present study, 32 patients with Cerebral Paralysis, of both the sex. Evaluations had been made daily before and after the therapy, using the scale of measurement of the thick motor function of patients GMFM (Gross Motor Function Measure), with 88 separate items in 5 dimensions. The instrument used for analyzes statistics was the SPSS13.0, with statistics of pair upped the sample (p
Keywords: Cerebral paralysis; Corporal Position marches; therapeutic horsebackriding